Applicability of Moyer’s prediction tables to estimate the mesio-distal diameter of canines and premolars - Amanda de Sousa Galdino (Dentistry 3000, 2019)
Objective: The aim of this study was to verify the applicability of Moyer’s prediction tables to estimate the mesio-distal diameter of canines and pre-molars in a population of North-Eastern Brazil. Materials and Methods: A sample of 100 plaster moulds of 12-18-year-old patients was selected from the dental archives of the Brazilian Association of Orthodontists Dental School Clinic in the city of João Pessoa, State of Paraiba. Analyses were performed with R software (version 3.1.3). The upper and lower canines and premolars on both sides of the arch were measured. Data Analysis: Linear regression analysis was used to assess the closeness of the estimated values in each percentile of Moyer’s prediction table.  Analyses were performed at a significance level of 5%. Results: Gender dimorphism (P < 0.001) was found in both upper and lower arches. In the upper arch, the best regression models for data analysis of female, male and both were, respectively, p5 and p6”, p25 and p35, and p35 and 75, whereas in the lower arch were p15, p35 and p75, with “p75 being the best-fitted percentile following application of correction equations for both genders. Conclusions: The Moyer’s prediction table can be applied for estimating the mesio-distal diameters of canines and pre-molars, provided that a correction factor is used for the population under study.